Herbal Medicine Filling Machine Type Rotary Conveyor System Based On Timer control - Dimas Ruri Assidiqi; Adi Rangga lesmana; Muhammad Ramadhon Fatmi; Dicky Viansyah Hadid; Muhammad Artian Pramudana (Journal of World Conference (JWC), 2020)
Based on the results of observations and interviews with partner SMEs, the process of filling herbal medicine into 350 ml syringe bottles was done manually, namely with the help of simple equipment such as 200 ml size cups and funnels. This causes the filling process to be around 9.49 seconds / bottle, filling in the herbal medicine is relatively inaccurate, employees tend to experience fatigue, and the SMEs often find it difficult to fulfill herbal orders in a short and many times. The purpose of this research is to increase the effectiveness in the production process of filling herbal medicine faster, hygienic and accurate. The methods of implementing this activity include observation with partners, literature study, manufacturing and machine assembly, testing and implementation. The results of the application obtained a capacity of 38 Liters, foodgrade stainless material, and the process of filling herbal medicine to 5.67 seconds / bottle